Exercice 1
Calculer les expressions suivantes en détaillant les calculs.
A = 12 − (3 + 5)
B = 7 × 8 + 13
C = 12 × 13 + 8
D = 5 + 11 × 4 + 3 ÷ 3 − 7
E = 5 × 13 − 8 + 10 + 12 ÷ 12
F = 11 ÷ 11 + 10 − 6 + 4 × 7
G = 6 ÷ 6 + 7 × 5 − (5 + 9)
H = 5 + 1,4 + 6 × 7 − 8,6
I = 6,8 ÷ 6,8 + 7,7 × (5,1 + 8,7)

2

Réponses

  • Utilisateur Brainly
2013-07-08T14:36:32+02:00

Bonjour,

 

A = 12 − (3 + 5)
A = 12 − 8
A = 4


B = 7 × 8 + 13
B = 56 + 13
B = 69


C = 12 × 13 + 8
C = 156 + 8
C = 164


D = 5 + 11 × 4 + 3 ÷ 3 − 7
D = 5 + 44 + 3 ÷ 3 − 7
D = 5 + 44 + 1 − 7
D = 49 + 1 − 7
D = 50 − 7
D = 43


E = 5 × 13 − 8 + 10 + 12 ÷ 12
E = 65 − 8 + 10 + 12 ÷ 12
E = 65 − 8 + 10 + 1
E = 57 + 10 + 1
E = 67 + 1
E = 68


F = 11 ÷ 11 + 10 − 6 + 4 × 7
F = 1 + 10 − 6 + 4 × 7
F = 1 + 10 − 6 + 28
F = 11 − 6 + 28
F = 5 + 28
F = 33


G = 6 ÷ 6 + 7 × 5 − (5 + 9)
G = 6 ÷ 6 + 7 × 5 − 14
G = 1 + 7 × 5 − 14
G = 1 + 35 − 14
G = 36 − 14
G = 22


H = 5 + 1,4 + 6 × 7 − 8,6
H = 5 + 1,4 + 42 − 8,6
H = 6,4 + 42 − 8,6
H = 48,4 − 8,6
H = 39,8


I = 6,8 ÷ 6,8 + 7,7 × (5,1 + 8,7)
I = 6,8 ÷ 6,8 + 7,7 × 13,8
I = 1 + 7,7 × 13,8

I = 1 + 106,26 

I = 107,26

 

en esperant t'avoir aider 

Meilleure réponse !
2013-07-08T14:42:58+02:00

A = 12 − (3 + 5)

   = 12- 8

   =4


B = 7 × 8 + 13

   =56+13

   =69


C = 12 × 13 + 8

   =156+8

   =164


D = 5 + 11 × 4 + 3 ÷ 3 − 7

   =5+44+1-7

   =50-7

   =43


E = 5 × 13 − 8 + 10 + 12 ÷ 12

   =65-8+10+1

   =57+10+1

   =68


F = 11 ÷ 11 + 10 − 6 + 4 × 7

   =1+10-6+28

   =1+4+28

   =33


G = 6 ÷ 6 + 7 × 5 − (5 + 9)

   =6/6+7*5-14

   =1+35-14

   =36-14

   =22


H = 5 + 1,4 + 6 × 7 − 8,6

   =5+1.4+42-8.6

   =48.4-8.6

   =39.8

   
I = 6,8 ÷ 6,8 + 7,7 × (5,1 + 8,7)

 = 6.8/6.8+7.7*13.8

 =1+106.26

 =107.26

 

voilààà :)